Effects of leaf quality and colonization time on the abundance of bacteria in an experimental design - Rasvailer, Vinícius da Silva; Gentilin-Avanci, Camila; Scoarize, Matheus Maximilian Ratz; Pinha, Gisele Daiane; Benedito, Evanilde (Acta Scientiarum. Biological Sciences, 2022)
Small rivers, henceforth streams, depend on organic matter (nutrients and energy) from riparian vegetation. The quality of such allochthonous debris is determinant for the transformation of organic matter compounds, where the bacterial community has a crucial role in the final decomposition of the substrate. During bacterial colonization, debris with higher concentration of nutrients (more palatable) is prioritized, which accelerates the process. This study investigated the effects of leaf palatability of two native trees on bacterial colonization (abundance) over time, through a laboratory experiment that lasted 60 days. Values of C, N, P, C:N, C:P, polyphenols, tannins, lignin, lignin:N and leaf toughness of both species were compared. Bacterial abundance was higher in species with higher nitrogen values, although they had higher leaf toughness and more polyphenols, which differs from studies indicating that high leaf toughness represents low nutritional quality. The colonization time did not influence bacterial abundance. Therefore, processes degrading riparian vegetation and reducing nutritional quality can affect local decomposition, decreasing bacterial abundance.